2012
DOI: 10.1186/1471-2164-13-s7-s19
|View full text |Cite
|
Sign up to set email alerts
|

The parasite specific substitution matrices improve the annotation of apicomplexan proteins

Abstract: Background A number of apicomplexan genomes have been sequenced successfully in recent years and this would help in understanding the biology of apicomplexan parasites. The members of the phylum Apicomplexa are important protozoan parasites (Plasmodium, Toxoplasma and Cryptosporidium etc) that cause some of the deadly diseases in humans and animals. In our earlier studies, we have shown that the standard BLOSUM matrices are not suitable for compositionally biased apicomplexan proteins. So we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…For instance, matrices specialized for transmembrane regions ( Muller et al , 2001 ; Ng et al , 2000 ) and for β-barrel membrane proteins ( Jimenez-Morales and Liang, 2011 ; Jimenez-Morales et al , 2008 ) have been developed. Matrices for particular proteins/organisms have also been constructed ( Ali et al , 2012 ; Brick and Pizzi, 2008 ; Dimmic et al , 2002 ; Kuznetsov, 2011 ; Lemaitre et al , 2011 ). Aside from those matrices, a general scheme for the compositional adjustment of matrices has been proposed ( Yu et al , 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, matrices specialized for transmembrane regions ( Muller et al , 2001 ; Ng et al , 2000 ) and for β-barrel membrane proteins ( Jimenez-Morales and Liang, 2011 ; Jimenez-Morales et al , 2008 ) have been developed. Matrices for particular proteins/organisms have also been constructed ( Ali et al , 2012 ; Brick and Pizzi, 2008 ; Dimmic et al , 2002 ; Kuznetsov, 2011 ; Lemaitre et al , 2011 ). Aside from those matrices, a general scheme for the compositional adjustment of matrices has been proposed ( Yu et al , 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…These have been used in structure-function predictions. Some other studies have shown that the use of protein-family-specific substitution matrices is helpful to identify orthologs that are not identifiable with the standard BLOSUM matrices 36 . Recently we also explored this approach, but have still obtained relatively small gains 37 .…”
Section: Introductionmentioning
confidence: 99%
“…These series of matrices were used in structure-function prediction. Some studies have shown that the use of protein family specific substitution matrices is helpful to identify orthologs that are not identified with the standard Blosum matrices [ 36 ]. In that study the authors developed parasite specific similarity matrices and were thereby able to annotate apicomplexan proteins which have unknown functions.…”
Section: Introductionmentioning
confidence: 99%